The effect of differing shaft dynamics on the biomechanics of the golf swing - Betzler, N. F. (2010)
The role of the shaft in the golf swing has been the subject of scientific debate for many years but there is little consensus regarding the effects of altering shaft bending stiffness. The aim of this thesis was to determine and explain the effects of changes in shaft stiffness on body kinematics, shaft strain and key performance indicators including club head speed, impact location on the club face and launch conditions. For this purpose, three clubs matched in all properties but shaft bending stiffness (l-flex (217 cpm), r-flex (245 cpm) and x-flex (272 cpm)) were instrumented with strain gauges. In an initial study, seventeen male golfers (handicap 1.8 ±1.9) tested these clubs, but no shaft effects on body kinematics, club head speed and ball launch conditions were identified. A follow-up study involved twenty skilled players (handicap 0.3 ±1.7), testing only the l- and x-flex clubs. Two optical motion capture systems were used to determine wrist angular kinematics, club head presentation and the ball`s impact location on the club face. There was an effect of shaft stiffness on ball and club head speed, both of which increased by 0.7 % for the l-flex club (p = 0.008 and < 0.001, respectively). Two factors contributed to these increases: (i) a faster recovery of the l-flex shaft from lag to lead bending just before impact (p < 0.001); (ii) an increase of 0.5 % in angular velocity of the grip of the l-flex club at impact (p = 0.005). A difference in angular wrist kinematics between the two clubs was identified for two swing events and may have contributed to the increase in angular velocity. The face angle (p = 0.176) and the ball`s impact location (p = 0.907 and p = 0.774) were unaffected by changes in shaft stiffness. Decreases in shaft stiffness were associated with significantly more shaft bending at the transition from backswing to downswing (p < 0.001), but the amount of lead bending at impact was found to be largely unaffected by shaft stiffness. The test protocol from the follow-up study was repeated using a golf robot, confirming the results for ball speed and wrist kinematics if the impact speed was set to replicate the mean club head speed achieved by the human players. Results from this thesis contradict the conventional view that reducing shaft stiffness leads to an increase in lead bending at impact and, consequently, to an increase in ball launch angle. Overall, these results suggest that it is unlikely that changes in overall shaft stiffness in themselves have a marked effect on driving performance.